Giant Fibroepithelial Polyps: Why do they Grow Excessively? - Can, Bilgen (Sisli Etfal Hastan Tip Bul, 2020)
Fibroepithelial polyps (acrochordon or skin tag) are benign tumors that usually occur in skin folds, such as the axilla, genital area or neck. They can be solitary or multiple. Their dimensions usually do not exceed 1-2 millimeters. Sometimes, they can reach huge dimensions. In the literature, a giant fibroepithelial polyp with a size of 42 centimeters has been reported. Although the etiology and the factors that cause excessive growth have not been elucidated, it is stated that obesity and insulin resistance might trigger growth. Lymphedematous fibroepithelial polyps described in recent years show that prolonged lymphatic stasis and chronic inflammation may lead to the growth of fibroepithelial polyps. We present a 21-year-old patient with a giant fibroepithelial polyp with a size of 14x6 centimeter, located in the midline on the anterior chest wall. To our knowledge, this is the first case in the literature, in this location, which makes our case unique. Herein, we presented our patient along with the review of current literature pertaining to the diagnosis and the treatment of fibroepithelial polyps (FEPs) and the factors leading to excessive growth.